Safety and immunogenicity of fully liquid and lyophilized formulations of an investigational trivalent group B streptococcus vaccine in healthy non-pregnant women: Results from a randomized comparative phase II trial. Issue 16 (3rd April 2020) - Beran, Jiri; Leroux-Roels, Geert; Van Damme, Pierre; de Hoon, Jan; Vandermeulen, Corinne; Al-Ibrahim, Mohamed; Johnson, Casey; Peterson, James; Baker, Sherryl; Seidl, Claudia; Dreisbach, Annette; Karsten, Annette; et al.
Highlights: Liquid and lyophilized formulations of a trivalent GBS vaccine were compared in non-pregnant women. 529 women received a fully liquid and 521 received a lyophilized formulation. Both formulations had acceptable tolerability and safety profiles. Both formulations induced an equivalent GBS serotype-specific immune response. Abstract: Background: We evaluated the safety and immunogenicity of liquid and lyophilized formulations of an investigational trivalent group B streptococcus (GBS) vaccine in non-pregnant women and assessed the formulations' equivalence in terms of serotype-specific immune response. Methods: This phase II, randomized, comparative, observer-blind trial enrolled healthy non-pregnant women 18–40 years of age. Women received a single dose of fully liquid (n = 529) or lyophilized (n = 521) trivalent GBS vaccine on day 1. Safety assessments were performed up to day 181 (study termination). Serotype Ia/Ib/III-specific immunoglobulin G (IgG) antibodies were measured in sera from women on day 1 (pre-vaccination) and day 31. Equivalence between the two formulations was demonstrated if the two-sided 95% confidence interval (CI) for the ratio (liquid/lyophilized) of the geometric mean concentrations (GMCs) on day 31 was contained in a (0.5, 2.0) interval for each serotype. Results: Solicited and unsolicited adverse events were reported at similar rates for both formulations. Serious adverse events were reported for six (1.1%) liquid GBS and nine (1.7%) lyophilized GBS vaccinated women, none of which were considered related to vaccination or fatal. On day 31, serotype-specific IgG concentrations were 8–16-fold higher than on day 1 in both groups. Equivalence of the liquid to the lyophilized formulation 30 days post-vaccination was demonstrated as the 95% CIs of the GMC ratios were within the pre-specified interval for the three serotypes: GMC ratios were 1.02 (95% CI: 0.79, 1.32) for serotype Ia, 0.93 (0.71, 1.21) for serotype Ib and 0.99 (0.76, 1.30) for serotype III. Conclusions: Both formulations of the investigational trivalent GBS vaccine had favorable safety profiles and induced similar GBS serotype-specific antibody concentrations. This study demonstrated that the fully liquid formulation was equivalent to the lyophilized formulation in healthy non-pregnant women in terms of immunogenicity for all three serotypes. Clinical Trials Registration: NCT02270944.